Study of Epidemiological Factors According to the Positive Response of IgG of Patients Infected With Blastocytsis Hominis in Diyala Province, Iraq - Muna Hameed Ahmed Alazzawi¹, Nabaa Ali Jasim², Masar H. Ismail³ (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Blastocystis hominis (B.hominis) is the most common intestinal parasite in humans and many other animals. Infections with the organism are spread worldwide and some of them have been asymptomatic, acute symptomatic and chronic.Materals and Method: 100 blood samples were collected from patients with B.hominis which were reviewing to some Hospital and health center in Diyala province during the period from October 2018 to March 2019. To determine the extent of IgG antibody responses in serum patients infected with B.hominis for depending on the chromatic changes resulting from the association of antigens with antibodies.Results: The results of the current study showed the percentage of infection among males was (56.25%), which is higher than that of females (43.75%), and the age group (3-6) years among males showed the highest rate of infection (33.34%) and the lowest in age groups less from one year and (9-12) years groups at (11.11%). The rate of infection in the age groups (1-3) years and (6-9) years was (22.22%) and in the age group of (1-3) years was the highest incidence among female groups (42.86%), while the age group (3-6) years showed less than that (28.57%) and significant differences at the level of probability less than (0.05). The percentage of B. hominis infection increased among the rural population by (56.5%), male infected, (57.14%) female, while the proportion of males among the urban population was (44.44%) and females reached (42.86%), with a standard deviation of (1.600 ± 0.495) and (1.480 ±0.505) respectively.Conclusions: The presence of immunoglobulin IgG in serum patients has been shown to stimulate the cellular immune response and be indicative of long-term immunity against pathogenic antigens.